Hydrocarbons Degradation in Crude-oil Polluted Patagonian Soils with Different Organic Matter Quality: Effect of added Organic amendment - Cecilia E. S. Alvaro; Andrea M. Torre; Norma S. Nudelman (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Microbiological remediation technologies of oil contaminated soils have proven one of the most efficient techniques, being an environmentally sustainable and cost-effective solution applied at oil contaminated soils. In our country, these processes are commonly performed by adding synthetic fertilizers and control of the environmental conditions process, such as landfarming method. This research study the efficacy of adding biosolids, the effects of soil organic matter (OM) and its association degree with added amendment in bioremediation process of two contrasting quality soils of Comahue region, North Patagonia, Argentine. The obtained results show a statistically significant difference in petroleum total hydrocarbons (TPH) degradation kinetics, where the higher reduction of TPH was obtained with the contribution of biosolids amendment. The heavy hydrocarbon fraction (HFP), considered resistant to biodegradation showed significant reductions, being biosolids an effective treatment. Volatile aromatic hydrocarbons, (BTEX), were eliminated rapidly, due to processes of volatilization and biodegradation. Organic amendment optimize microbial activity producing significant improvement over conventional landfarming treatments. Results presented suggest that the OM soil and amendment markedly interact to determine the degradation rate of hydrocarbons in oil-polluted soil. To date there have been no studies to assess the impact caused by oil spills in high OM content soils of Comahue region, and the behaviour of these soil on degradation oil spills.